Low-carbon energy-saving fiberboard and preparation method thereof
By using industrial solid waste and recycled paper to prepare low-carbon energy-saving fiberboard, the problems of industrial solid waste treatment and carbon dioxide emissions are solved, the dual goals of environmental protection and economic benefits are achieved, and the performance of the board is improved.
Patent Information
- Application Number
- CN202510033156.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-04-29
AI Technical Summary
The prior art is difficult to effectively deal with industrial solid waste and reduce carbon dioxide emissions in industrial exhaust, resulting in intensification of environmental pollution and greenhouse effects.
By utilizing industrial solid waste and recycled paper, a low-carbon energy-saving fiberboard is prepared. The preparation method of the fiberboard includes grinding premix, alkali excitation reaction, modifier enhancement, steam normal pressure curing and carbonization treatment, and carbonization using industrial exhaust gas rich in carbon dioxide.
The effective utilization of industrial solid waste and carbon dioxide emission reduction have been achieved, the production cost of fiberboard is reduced, and the mechanical properties and water resistance of the plate are improved.
Smart Images

Figure BDA0005234741110000081
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of building materials, and particularly relates to a low-carbon energy-saving fiberboard and a preparation method thereof. Background Art
[0002] In the process of modern industrial production, a large amount of solid waste and industrial tail gas will inevitably be generated. These solid wastes, such as steel slag, fly ash, desulfurized gypsum, quartz tail mud, etc., if not properly handled, will not only occupy precious land resources, but also cause serious pollution to the environment. At the same time, industrial tail gas contains a large amount of carbon dioxide gas, and its large-scale emission not only aggravates the greenhouse effect, but also runs counter to the current low-carbon environmental protection concept advocated. Therefore, the development of a product and its preparation method that can effectively treat industrial solid waste and reduce industrial tail gas carbon emissions is of great significance for reducing the adverse effects of solid waste on the environment and reducing carbon dioxide emissions. Summary of the invention
[0003] The purpose of the present invention is to achieve the dual goals of environmental protection and economic benefit improvement by utilizing industrial solid waste and recycled paper.
[0004] To this end, the present invention provides a low-carbon energy-saving fiberboard, which includes, by weight: 8-38 parts of steel slag, 12-36 parts of fly ash, 0-20 parts of cement, 10-48 parts of desulfurized gypsum, 2-4 parts of silica fume, 3-9 parts of quartz tailings, 6-10 parts of dry pulp fiber, 0.1-0.48 parts of gypsum retarder, 0.48-1.20 parts of alkali activator, and 0.01-4.32 parts of modifier.
[0005] Specifically, the dry pulp fibers include virgin pulp fibers and recycled pulp fibers; the recycled pulp fiber content is 30%-70% by mass.
[0006] Specifically, the alkaline activator is composed of NaOH and water glass, and the modulus is 1.0-1.25.
[0007] Specifically, the above-mentioned modifier includes any one of sodium methyl silicate, polymethyltriethoxysilane, and fluorosilicone emulsion.
[0008] Specifically, the steel slag is prepared by the following steps: grinding the steel slag to a specific surface area of 450-500m 2 / kg, add 9-11% water and mix, and carbonize at 60-80℃ for 2-4h.
[0009] The present invention also provides a method for preparing the above-mentioned carbon energy-saving fiberboard, comprising the following steps:
[0010] S1, weighing powder materials according to the proportion, grinding and premixing, and grinding the pulp fibers;
[0011] S2, adding water to the premixed powder, pulp, alkali activator, and modifier to mix and prepare a slurry;
[0012] S3, slurry dehydration to prepare slab, slab pressurization forming, steam normal pressure curing, pre-drying;
[0013] S4, sending the slab into a carbonization device for carbonization to obtain a fiberboard.
[0014] Specifically, the slurry concentration is 15-18%.
[0015] Specifically, in the above step S3, the slab is cured under normal pressure and steam at 60-80° C. for 8-24 hours.
[0016] Specifically, in the above step S3, the moisture content of the slab after pre-drying is controlled at 10-15%.
[0017] Specifically, the above step S4 is as follows: sending the slab into the carbonization equipment, introducing industrial tail gas rich in carbon dioxide, with the concentration of carbon dioxide being ≥5%, and the carbonization time being controlled within 2h-24h.
[0018] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0019] The low-carbon energy-saving fiberboard and preparation method thereof provided by the present invention use solid waste as the main material, use alkaline activators to stimulate the reaction of fly ash, quartz tailings, silica ash with steel slag, cement and desulfurized gypsum, promote the formation of minerals such as calcium aluminum sulfate, enhance the water resistance of gypsum-based products through modifiers, and use recycled paper with easy-to-grind and short fiber characteristics to replace part of the original paper, which not only reduces the production cost of the fiberboard, but also makes the pulp fiber length and short match, effectively improves the fiber orientation distribution, and improves the longitudinal and transverse flexural strength of the board. Pre-carbonization of steel slag can effectively eliminate free calcium oxide and magnesium oxide in steel slag, and reduce the damage to the structure caused by the late hydration expansion of active alkali. Then, the uncarbonized tricalcium silicate and dicalcium silicate in the material are hydrated to form hydrated calcium silicate, calcium aluminum sulfate and other minerals through steam normal pressure curing. In addition, the use of steam normal pressure curing combined with carbonization curing can reduce the cost expenditure of the autoclave curing stage. DETAILED DESCRIPTION
[0020] The technical scheme in the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Although the representative embodiments of the present invention have been described in detail, it will be understood by those skilled in the art that various modifications and changes can be made to the present invention without departing from the scope of the present invention. Therefore, the scope of the present invention should not be limited to the embodiments, but should be limited by the attached claims and their equivalents.
[0021] The present invention provides a low-carbon energy-saving fiberboard, which comprises, by weight: 8-38 parts of steel slag, 12-36 parts of fly ash, 0-20 parts of cement, 10-48 parts of desulfurized gypsum, 2-4 parts of silica fume, 3-9 parts of quartz tailings, 6-10 parts of dry pulp fibers, 0.1-0.48 parts of gypsum retarder, 0.48-1.2 parts of alkali activator, and 0.01-4.32 parts of modifier.
[0022] The dry pulp fibers include virgin pulp fibers and recycled pulp fibers; the recycled pulp fiber content is 30%-70% by mass, and the recycled paper is mainly composed of paper products made from coniferous wood pulp such as waste kraft paper, paper bags, and kraft linerboard; the alkali activator is composed of NaOH and water glass, and the modulus is 1.0-1.25; the modifier includes any one of sodium methyl silicate, polymethyltriethoxysilane, and fluorosilicone emulsion; the steel slag is preferably pre-carbonized steel slag, which is prepared by the following steps: grinding the steel slag to a specific surface area of 450-500m 2 / kg, add 9-11% water and mix, and carbonize at 60-80℃ for 2-4h.
[0023] The present invention also provides a method for preparing the above-mentioned carbon energy-saving fiberboard, comprising the following steps:
[0024] S1. Weigh steel slag, fly ash, desulfurized gypsum, quartz tailings, cement, gypsum retarder and other powders according to weight and grind them for 10-20 minutes.
[0025] Recycled paper and virgin paper are weighed in proportion, and the pulp is ground to a beating degree of 25-33°SR and a wet weight of 8-13 g to obtain pulp.
[0026] S2. Add water to the premixed powder, pulp, alkali activator and modifier to mix and prepare a slurry with a concentration of 15-18%.
[0027] S3. Dehydrate the slurry by vacuum filtration or other feasible methods to prepare a slab. Pressurize the slab to a molding pressure of 20-25 MPa. Curing the slab at 60-80°C with steam at normal pressure for 8-24 hours. Pre-dry the cured slab at a drying temperature of preferably 30-60°C, and control the moisture content of the slab to 10-15%.
[0028] S4. Send the slab into the carbonization equipment, introduce industrial tail gas rich in carbon dioxide, the concentration of carbon dioxide is ≥5%, the tail gas can be pressurized by the booster equipment, the carbonization time is controlled at 2h-24h, and the fiberboard is obtained. The board is post-processed according to the demand.
[0029] The effects of the low-carbon energy-saving fiberboard and the preparation method thereof of the present invention are studied through specific examples below.
[0030] Embodiment 1:
[0031] The present embodiment provides a low-carbon energy-saving fiberboard, which includes, by weight: 8 parts of steel slag, 12 parts of fly ash, 12 parts of cement, 48 parts of desulfurized gypsum, 4 parts of silica ash, 9 parts of quartz tailings, 7 parts of dry pulp fiber, 0.48 parts of gypsum retarder, 0.48 parts of alkali activator, and 0.1 parts of modifier.
[0032] The dry pulp fibers include virgin paper and recycled paper; the recycled paper content is 30% by mass, and the recycled paper is waste kraft paper; the alkaline activator consists of NaOH and water glass, and the modulus is 1.0; and the modifier is 0.1 parts of sodium methyl silicate.
[0033] This embodiment also provides a method for preparing the low-carbon energy-saving fiberboard, comprising the following steps:
[0034] S1. Grind the steel slag to a specific surface area of 450m 2 / kg, add 9% water and mix, and carbonize at 60℃ for 4h.
[0035] Pre-carbonized steel slag, fly ash, desulfurized gypsum, quartz tailings, cement, gypsum retarder and other powders were weighed according to weight proportions and ground for 10 minutes.
[0036] Dry recycled paper and virgin paper were weighed in proportion, and pulped to a beating degree of 25°SR and a wet weight of about 13 g to obtain pulp.
[0037] S2. Add water to the premixed powder, pulp, alkali activator and modifier to mix and prepare a slurry with a concentration of 15%.
[0038] S3. Dehydrate the slurry by vacuum filtration or other feasible methods to prepare a slab. Pressurize the slab to a molding pressure of 25 MPa. Curing the slab at 60°C under steam pressure for 24 hours. Pre-dry the cured slab at 45°C to control the moisture content of the slab at 15%.
[0039] S4. Send the slab into the carbonization equipment, introduce industrial tail gas rich in carbon dioxide, the concentration of carbon dioxide is ≥5%, and the tail gas is pressurized by the booster equipment. The carbonization time is controlled at 2 hours to obtain the fiberboard.
[0040] The fiberboard was tested for performance and the results are shown in Table 1.
[0041] Embodiment 2:
[0042] The present embodiment provides a low-carbon energy-saving fiberboard, which includes, by weight: 38 parts of steel slag, 36 parts of fly ash, 10 parts of desulfurized gypsum, 4 parts of silica ash, 3 parts of quartz tailings, 9 parts of dry pulp fiber, 0.1 parts of gypsum retarder, 1.2 parts of alkali activator, and 0.01 parts of modifier.
[0043] The dry pulp fibers include virgin paper and recycled paper; the recycled paper content is 60% by mass, and the recycled paper is waste kraft paper; the alkaline activator is composed of NaOH and water glass, and the modulus is 1.25; and the modifier is 0.01 parts of polymethyltriethoxysilane.
[0044] This embodiment also provides a method for preparing the low-carbon energy-saving fiberboard, comprising the following steps:
[0045] S1. Grind the steel slag to a specific surface area of 500m 2 / kg, add 10% water and mix, and carbonize at 80℃ for 2h.
[0046] Pre-carbonized steel slag, fly ash, desulfurized gypsum, quartz tailings, gypsum retarder and other powders were weighed according to weight proportions and ground for 20 minutes.
[0047] Recycled paper and virgin paper were weighed in proportion, and pulped to a beating degree of 33°SR and a wet weight of 9 g to obtain pulp.
[0048] S2. Add water to the premixed powder, pulp, alkali activator and modifier to mix and prepare a slurry with a concentration of 18%.
[0049] S3. Dehydrate the slurry by vacuum filtration or other feasible methods to prepare a slab. Pressurize the slab to a molding pressure of 20 MPa. Curing the slab at 80°C under steam pressure for 8 hours. Pre-dry the cured slab at 60°C to control the moisture content of the slab at 10%.
[0050] S4. Send the slab into the carbonization equipment, introduce industrial tail gas rich in carbon dioxide, the concentration of carbon dioxide is ≥5%, and the tail gas is pressurized by the booster equipment. The carbonization time is controlled at 12 hours to obtain the fiberboard.
[0051] The fiberboard was tested for performance and the results are shown in Table 1.
[0052] Embodiment 3:
[0053] The present embodiment provides a low-carbon energy-saving fiberboard, which includes, by weight: 25 parts of steel slag, 25 parts of fly ash, 18 parts of cement, 15 parts of desulfurized gypsum, 2 parts of silica ash, 9 parts of quartz tailings, 6 parts of pulp fiber, 0.15 parts of gypsum retarder, 0.81 parts of alkali activator, and 0.1 parts of modifier.
[0054] The pulp fibers include virgin paper and recycled paper; the recycled paper content is 70% by mass, and the recycled paper is waste kraft paper; the alkaline activator is composed of NaOH and water glass, and the modulus is 1.0; and the modifier is 0.1 parts of polymethyltriethoxysilane.
[0055] This embodiment also provides a method for preparing the low-carbon energy-saving fiberboard, comprising the following steps:
[0056] S1. Grind the steel slag to a specific surface area of 450m 2 / kg, add 10% water and mix, and carbonize at 70℃ for 3h.
[0057] Pre-carbonized steel slag, fly ash, desulfurized gypsum, quartz tailings, cement, gypsum retarder and other powders were weighed according to weight proportions and ground for 15 minutes.
[0058] Recycled paper and virgin paper were weighed in proportion, and pulped to a beating degree of 25°SR and a wet weight of 8 g to obtain pulp.
[0059] S2. Add water to the premixed powder, pulp, alkali activator and modifier to mix and prepare a slurry with a concentration of 16%.
[0060] S3. Dehydrate the slurry by vacuum filtration or other feasible methods to prepare a slab. Pressurize the slab to a molding pressure of 20 MPa. Curing the slab at 70°C under steam pressure for 16 hours. Pre-dry the cured slab at 55°C to control the moisture content of the slab at 12%.
[0061] S4. Send the slab into the carbonization equipment, introduce industrial tail gas rich in carbon dioxide, the concentration of carbon dioxide is ≥5%, and the tail gas is pressurized by the booster equipment. The carbonization time is controlled at 12 hours to obtain the fiberboard.
[0062] The fiberboard was tested for performance and the results are shown in Table 1.
[0063] Embodiment 4:
[0064] The present embodiment provides a low-carbon energy-saving fiberboard, which includes, by weight: 8 parts of steel slag, 20 parts of fly ash, 20 parts of cement, 32 parts of desulfurized gypsum, 4 parts of silica ash, 9 parts of quartz tailings, 7 parts of pulp fiber, 0.32 parts of gypsum retarder, 0.72 parts of alkali activator, and 4.32 parts of modifier.
[0065] The pulp fibers include virgin paper and recycled paper; the recycled paper content is 50% by mass, and the recycled paper is waste kraft paper; the alkaline activator is composed of NaOH and water glass, and the modulus is 1.0; the modifier is 4.32 parts of fluorosilicone emulsion.
[0066] This embodiment also provides a method for preparing the low-carbon energy-saving fiberboard, comprising the following steps:
[0067] S1. Grind the steel slag to a specific surface area of 450m 2 / kg, add 9% water and mix, and carbonize at 60℃ for 4h.
[0068] Pre-carbonized steel slag, fly ash, desulfurized gypsum, quartz tailings, cement, gypsum retarder and other powders were weighed according to weight proportions and ground for 10 minutes.
[0069] Recycled paper and virgin paper were weighed in proportion, and pulped to a beating degree of 25°SR and a wet weight of 8 g to obtain pulp.
[0070] S2. Add water to the premixed powder, pulp, alkali activator and modifier to mix and prepare a slurry with a concentration of 15%.
[0071] S3. Dehydrate the slurry by vacuum filtration or other feasible methods to prepare a slab. Pressurize the slab to a molding pressure of 25 MPa. Curing the slab at 60°C under steam pressure for 24 hours. Pre-dry the cured slab at 45°C to control the moisture content of the slab at 15%.
[0072] S4. Send the slab into the carbonization equipment, introduce industrial tail gas rich in carbon dioxide, the concentration of carbon dioxide is ≥5%, and the tail gas is pressurized by the booster equipment. The carbonization time is controlled at 2 hours to obtain the fiberboard.
[0073] The fiberboard was tested for performance and the results are shown in Table 1.
[0074] Comparative Example 1:
[0075] This comparative example provides a fiberboard, which includes, by weight: 38 parts of cement, 50 parts of quartz sand, 5 parts of sanding powder, and 7 parts of pulp fibers, wherein all the pulp fibers are virgin paper and do not contain recycled paper.
[0076] This comparative example also provides a method for preparing the above fiberboard, comprising the following steps:
[0077] S1. Weigh cement, quartz sand and sanding powder according to weight and premix.
[0078] Raw paper was weighed according to the proportion, and was refined to a beating degree of 25°SR and a wet weight of 14 g to obtain pulp.
[0079] S2. Add water to the premixed powder and pulp to make a slurry with a concentration of 15%.
[0080] S3. Dehydrate the slurry by vacuum filtration or other feasible methods to prepare a slab. Pressurize the slab to a molding pressure of 16 MPa. Curing the slab at 60°C under steam pressure for 24 hours. Pre-dry the cured slab at 45°C to control the moisture content of the slab at 15%.
[0081] S4. Send the slab into the carbonization equipment, introduce industrial tail gas rich in carbon dioxide, the concentration of carbon dioxide is ≥5%, and the tail gas is pressurized by the booster equipment. The carbonization time is controlled at 2 hours to obtain the fiberboard.
[0082] The fiberboard was tested for performance and the results are shown in Table 1.
[0083] Comparative Example 2:
[0084] This comparative example provides a fiberboard, which is different from Example 1 only in that the pulp fibers are all virgin paper and do not contain recycled paper, and the preparation method is the same as that of Example 1.
[0085] Comparative Example 3:
[0086] This comparative example provides a fiberboard, which is different from Example 1 only in that the steel slag is not carbonized. The fiberboard preparation method is the same as that of Example 1.
[0087] Table 1 Fiberboard performance parameters
[0088]
[0089] It can be seen from Table 1 that under the conditions of using solid waste and non-autoclaving curing, the mechanical properties of the board provided by the present invention are close to or exceed those of the comparative board, the longitudinal and transverse flexural strength ratio is increased by about 10%, and the overall production cost is reduced by about 10%.
[0090] The above examples are merely illustrative of the present invention and do not constitute a limitation on the protection scope of the present invention. All designs that are the same or similar to the present invention fall within the protection scope of the present invention.
Claims
1. A low-carbon energy-saving fiberboard, characterized in that: Calculated by weight, it includes: 8-38 parts of steel slag, 12-36 parts of fly ash, 0-20 parts of cement, 10-48 parts of desulfurized gypsum, 2-4 parts of silica fume, 3-9 parts of quartz tailings, 6-10 parts of dry pulp fiber, 0.1-0.48 parts of gypsum retarder, 0.48-1.20 parts of alkali activator, and 0.01-4.32 parts of modifier.
2. The low-carbon energy-saving fiberboard according to claim 1, characterized in that: The dry pulp fibers include virgin pulp fibers and recycled pulp fibers; the recycled pulp fiber content is 30%-70% by mass.
3. The low-carbon energy-saving fiberboard according to claim 1, characterized in that: The alkaline activator consists of NaOH and water glass, and has a modulus of 1.0-1.
25.
4. The low-carbon energy-saving fiberboard according to claim 1, characterized in that: The modifier includes any one of sodium methyl silicate, polymethyltriethoxysilane and fluorosilicone emulsion.
5. The low-carbon energy-saving fiberboard according to claim 1, characterized in that: The steel slag is prepared by the following steps: grinding the steel slag to a specific surface area of 450-500m 2 / kg, add 9-11% water and mix, and carbonize at 60-80℃ for 2-4h.
6. The method for preparing the low-carbon energy-saving fiberboard according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1, weighing powder materials according to the proportion, grinding and premixing, and grinding the pulp fibers; S2, adding water to the premixed powder, pulp, alkali activator, and modifier to mix and prepare a slurry; S3, dehydrating the slurry to prepare a slab, and after the slab is pressurized and formed, steam is used for normal pressure curing and pre-drying; S4, sending the slab into a carbonization device for carbonization to obtain a fiberboard.
7. The method for preparing the low-carbon energy-saving fiberboard according to any one of claims 6, characterized in that: The slurry concentration is 15-18%.
8. The method for preparing the low-carbon energy-saving fiberboard according to any one of claims 6, characterized in that: In step S3, the slab is cured under normal pressure and steam at 60-80° C. for 8-24 hours.
9. The method for preparing the low-carbon energy-saving fiberboard according to any one of claims 6, characterized in that: In the step S3, the moisture content of the slab after pre-drying is controlled at 10-15%.
10. The method for preparing the low-carbon energy-saving fiberboard according to any one of claim 6, characterized in that: The step S4 specifically includes: sending the slab into the carbonization equipment, introducing industrial tail gas rich in carbon dioxide, the concentration of carbon dioxide being ≥5%, and the carbonization time being controlled within 2h-24h.
Citation Information
Cited By
Carbon-alkali in-situ synergistically excited multi-element solid waste-based carbon sequestration cementing material, product and preparation method
CN121405384A